2D DIGE proteomic analysis of early post mortem muscle exudate highlights the importance of the stress response for improved water‐holding capacity of fresh pork meat. Issue 9 (18th April 2013) - Di Luca, Alessio; Elia, Giuliano; Hamill, Ruth; Mullen, Anne Maria
<x xml:space="preserve">Abstract</x> Variation in water‐holding capacity (WHC), which presents a major economic burden to the swine industry, is considered to be underpinned by variation at a molecular and biochemical level. High‐resolution 2D DIGE followed by MS analysis and Western blot were used to unravel the proteome of muscle exudate, collected following centrifugation, in the pH 4–7 range. A first 2DE‐based protein map of this substrate was produced where 89 spots were successfully characterised. Two phenotypes divergent for WHC plus one intermediate were compared with a view to deciphering the biochemical processes impacting on variation in WHC. Twenty spots were observed to be altered across the phenotypes. Of these, 14 represented sixteen proteins including metabolic enzymes, stress response proteins and structural proteins. Triosephosphate isomerase and transferrin showed a major difference between the two extreme phenotypes, and may have potential as biological markers for WHC prediction. Several members of the HSPs family were highlighted. This proteomic study makes an important contribution towards a more detailed molecular view of the processes behind WHC and will provide a valuable resource for future investigations.